Assessment of delirium in children admitted into the Intensive Care Unit: psCAM-ICU Tool - Ángela María Henao Castaño; Edwar Yamith Pinzon Casas (Universidad Nacional de Colombia, 2020)
Background: Delirium has been identified as a risk factor for the mortality of critically ill patients, generating great social and economic impacts, since patients require more days of mechanical ventilation and a prolonged hospital stay in the intensive care unit (ICU), thus increasing medical costs. Objective: To describe the prevalence and characteristics of delirium episodes in a sample of 6-month to 5-year-old children who are critically ill. Methods: Cohort study at a Pediatric Intensive Care Unit (PICU) in Bogotá (Colombia). Participants were assessed by the Preschool Confusion Assessment Method for the ICU (psCAM-ICU) within the first twenty-four hours of hospitalization. Results: One quarter of the participants (25.8%) presented some type of delirium. Among them, two sub-types of delirium were observed: 62.5% of the cases were hypoactive and 37.5% hyperactive. Moreover, from them, six were male (75%) and 2 female (25%). Primary diagnosis was respiratory tract infection in 62.55% of the patients, while respiratory failure was diagnosed in the remaining 37.5%. Conclusions: The implementation of delirium monitoring tools in critically ill children provides a better understanding of the clinical manifestation of this phenomenon and associated risk factors in order to contribute to the design of efficient intervention strategies.